Keterampilan Menulis Kalimat Sederhana Bahasa Jerman - Andrian Asri; Misnawaty Usman; Misnah Mannahali (Universitas Negeri Makassar, 2021)
Abstract. This research is a quantitative descriptive study that aims to determine the level of students' writing skills in simple sentences. The population in this study were students of class XI SMA Negeri 1 Makassar, totaling 360 students from 12 classes. The sample of this research is the students of class XI MIPA 1 SMAN 1 Makassar, totaling 30 students with random sampling. The research data was obtained through a simple sentence writing skill test and a questionnaire. The data were analyzed using the percentage technique. The results of the study of students' writing skills in simple sentences were in the very good category (91%). The results of the questionnaire from students' opinions stated that it was important in practicing German writing skills (76.7%) as an external factor.